2012
DOI: 10.2147/opth.s33595
|View full text |Cite
|
Sign up to set email alerts
|

Commercially available rigid gas-permeable contact lens for protecting the cornea from drying during vitrectomy with a wide viewing system

Abstract: PurposeWe evaluated the usefulness of commercially available materials for protecting the cornea from drying during vitrectomy with a wide-angle viewing system.MethodsThree vitreoretinal surgeons evaluated fundus visibility during vitrectomy on the images of five study materials used on the cornea: balanced saline solution, a viscoelastic agent, a vitrectomy contact lens, a rigid gas permeable (RGP) contact lens, and a soft contact lens. Fundus visibility was graded using the following scale: grade 1, unclear;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The CL designed by Chihara and Kita 10 is bigger, but its posterior curve radius and optical zone diameter do not accurately match in clinical practice, which could lead to incomplete filling of viscoelastic agents and bubbles under the CL. Kamei et al 11 reported that soft CLs might curl on the cornea and dry after a few minutes during the surgery. Commercial rigid gas-permeable (RGP) lenses provide the same clear vision as BSS, Viscoat, and vitrectomy lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The CL designed by Chihara and Kita 10 is bigger, but its posterior curve radius and optical zone diameter do not accurately match in clinical practice, which could lead to incomplete filling of viscoelastic agents and bubbles under the CL. Kamei et al 11 reported that soft CLs might curl on the cornea and dry after a few minutes during the surgery. Commercial rigid gas-permeable (RGP) lenses provide the same clear vision as BSS, Viscoat, and vitrectomy lenses.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 However, a lens holder or a fixation ring is necessary when using this procedure. While a rigid gas-permeable contact lens for myopia has also been reported to be ideal, 7 it is designed to be movable on the cornea in order to prevent hypoxic damage during daily use. Therefore, this would be a disadvantage when performing vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In their system, a magnifying contact lens is held on the cornea using a lens holder or a fixating ring. Kamei et al6 compared a commercially available rigid gas-permeable contact lens (−3 diopters) with a system that used a balanced salt solution, a viscoelastic agent, a vitrectomy contact lens, and a soft contact lens, and found the rigid gas-permeable contact lens to be ideal for use during vitrectomy when performed with a wide-angle viewing system. The rigid gas-permeable contact lens is designed to be movable on the cornea in order to prevent hypoxic corneal damage in daily use.…”
Section: Discussionmentioning
confidence: 99%